Syekh Wali Lanang sebagai PitÄmaha Raja Raja Jawa Studi Teks Babad GÄ•dhongan - Taufiq Hakim (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
The position of pitÄmaha or ancestor in the Babad tradition has an important role. One of them is the position of Sheikh Wali Lanang in Babad GÄ•dhongan (hereinafter abbreviated as BG). The guardian of the prophet's teachings is narrated later by the king of Java. This research seeks to understand the position of Sheikh Wali Lanang as the pitÄmaha of Javaâ€™s king in BG, a Javanese manuscript not yet widely known by the public generally. By presenting the historiography of Babad as a reconstructive historical source, and revealing the BG text philologically, it can be argued that the position of Sheikh Wali Lanang is a symbolic political movement by Paku Buwana III and Paku Buwana VII. The creation and transformation of BG are one of the kingdom's efforts to build a spiritual and spiritual culture after the fading of economic and political legitimacy resulting from the turmoil that occurred before. These two Surakarta kings indirectly also want to present themselves as the descendants of the Prophet, through Sheikh Wali Lanang who is the 21st descendant of the Prophet.Â